2018
DOI: 10.4314/jasem.v22i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model for the control of infectious disease

Abstract: ABSTRACT:We proposed a mathematical model of infectious disease dynamics. The model is a system of first order ordinary differential equations. The population is partitioned into three compartments of Susceptible ) (t S , Infected ) (t I and Recovered ) (t R . Two equilibria states exist: the disease-free equilibrium which is locally asymptotically stable if Ro < 1 and unstable if Ro > 1. Numerical simulation of the model shows that an increase in vaccination leads to low disease prevalence in a population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…However, after these few days, an inflexion point is reached and then the population begins to increase steadily for the remaining 100 days due to the loss of immunity of the recovered human population. This result is in agreement with the results of [20] and [6]. It can be observed that an increase in the contracting rate of the susceptible class via contact with the carrier class, , leads to a decrease in the population of this compartment.…”
Section: Numerical Simulations and Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, after these few days, an inflexion point is reached and then the population begins to increase steadily for the remaining 100 days due to the loss of immunity of the recovered human population. This result is in agreement with the results of [20] and [6]. It can be observed that an increase in the contracting rate of the susceptible class via contact with the carrier class, , leads to a decrease in the population of this compartment.…”
Section: Numerical Simulations and Discussion Of Resultssupporting
confidence: 92%
“…This result is in slight contrast with those in previous literatures. According to [3] and [20], the infected human compartment experiences a rapid increase between time 0 and 5. This increase was ascribed to the progression from the susceptible human population to the infected human population.…”
Section: Infected Human Populationmentioning
confidence: 99%
“…In 1927, W.O. Kermack and A.G. McKendrick proposed a complete mathematical model [15] to investigate the spread of infectious diseases by studying the Black Death that ravaged London in the 17th century and the plague that was prevalent in Mumbai in the early 20th century, and established an infectious disease warehouse model—the SIR infectious disease model [16] . Subsequently, numerous scientists studying epidemic diseases presented different models, in addition to the SIR model.…”
Section: Related Workmentioning
confidence: 99%
“…Coronavirus belong to a group of viruses that infect and causes diseases in human and other animals. It is thought that the virus might be of bat origin, and the transmission of the virus might be linked to a seafood market exposure named as Huanan Seafood Wholesale Market in Wuhan, where sold meat and live animals [22]. The World Health Organization (WHO), China Country Office discovered a case of pneumonia of unknown aetiology, first detected in Wuhan city, Hubei province in China on December 2019 [3] [23].…”
Section: Introductionmentioning
confidence: 99%